2021
DOI: 10.1111/ejn.15522
|View full text |Cite
|
Sign up to set email alerts
|

The effects of levodopa in the spatiotemporal gait parameters are mediated by self‐selected gait speed in Parkinson's disease

Abstract: In individuals with Parkinson's disease (PD), the medication induces different and inconsistent results in the spatiotemporal parameters of gait, making it difficult to understand its effects on gait. As spatiotemporal gait parameters have been reported to be affected by gait speed, it is essential to consider the gait speed when studying walking biomechanics to interpret the results better when comparing the gait pattern of different conditions. Since the medication alters the self-selected gait speed of indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
1
6
1
Order By: Relevance
“…This finding contrasts with previous studies, and it is likely attributed to the utilization of a suprathreshold LD dose in this study, which may have been lacking in the later studies. 10,11,14 In this study, a supra-physiologic response was observed for specific features, particularly those related to the upper arms. This observation leads us to believe that this supra-physiologic response likely reflects the presence of dyskinesia, which further reinforces the concept of a heightened susceptibility of the upper limbs to dopamine denervation and replenishment.…”
Section: Pd Gait Can Only Be Partially Rescued To a "Normal" Phenotypementioning
confidence: 59%
“…This finding contrasts with previous studies, and it is likely attributed to the utilization of a suprathreshold LD dose in this study, which may have been lacking in the later studies. 10,11,14 In this study, a supra-physiologic response was observed for specific features, particularly those related to the upper arms. This observation leads us to believe that this supra-physiologic response likely reflects the presence of dyskinesia, which further reinforces the concept of a heightened susceptibility of the upper limbs to dopamine denervation and replenishment.…”
Section: Pd Gait Can Only Be Partially Rescued To a "Normal" Phenotypementioning
confidence: 59%
“…Pharmacological interventions were recently addressed in a Cochrane review 21 . The effectiveness of two classes of non‐dopaminergic medications were examined, as no studies existed on the effects of levodopa on falls risk 77 . Nevertheless, levodopa has been shown to ameliorate some components of gait and balance dysfunction and may mediate fall risk indirectly 17 .…”
Section: Resultsmentioning
confidence: 99%
“… 21 The effectiveness of two classes of non‐dopaminergic medications were examined, as no studies existed on the effects of levodopa on falls risk. 77 Nevertheless, levodopa has been shown to ameliorate some components of gait and balance dysfunction and may mediate fall risk indirectly. 17 Direct studies of other agents on falls (including dopamine agonists, COMT‐inhibitors, amantadine, rasagiline, selegiline, methylphenidate) did not yield any studies examining falls as a primary outcome.…”
Section: Resultsmentioning
confidence: 99%
“…At present, research exploring medication and mobility in PwP is typically conducted in controlled lab-based or clinical environments, in specific ON/OFF medication states. [8][9][10][11][12][13][14][15][16] Although some studies have been performed in the real world (ie, daily living, outside clinical or laboratory settings), 17 18 a more granular picture is required.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%